Cross-asset dynamics: the interplay of oil, gas, wheat, and emerging market stock index in diversified portfolios - Wafa Kammoun Masmoudi; Nadia Belkhir (Cogent Business & Management)
This study explores the evolving interconnections between key commodity markets (Oil, Gas, Wheat) and emerging market stock indices over the period January 2016 to November 2022, which encompasses the COVID-19 pandemic and the Russia–Ukraine conflict. Utilizing the Dynamic Conditional Correlation (DCC) model—selected for its strength in capturing time-varying relationships without relying on rolling-window estimations.—we introduce and apply Volatility Impulse Response Functions (VIRFs). This approach allows for a nuanced examination of how shocks propagate across these markets over time. Our results reveal significant and fluctuating spillover effects, identifying Oil as the main net transmitter of shocks, followed by Natural Gas, while Wheat consistently appears as a net receiver. To assess portfolio implications, we statistically estimate optimal hedge ratios and portfolio weights based on the dynamic correlations. These findings offer practical guidance for investors seeking to improve portfolio diversification and risk management in times of heightened uncertainty.